Comparative Potential of Cream Preparations As Tyrosinase Inhibition Between Ethanolic Extracts of Kepel Leaves (Stelechocarpus burahol (Blume) Hook f. & Thomson) and Pulasari Bark (Alyxia reinwardii Blume) - Endang Dwi Wulansari; Endang Diyah Ikasari; Adilah Athtahirah; Dharu Fajar Dwikha Timronna (Indonesian Journal of Pharmacy and Natural Product, 2025)
The problem of skin hyperpigmentation due to excessive exposure to ultraviolet rays is a primary concern in the development of cosmetic preparations based on natural ingredients. The enzyme tyrosinase plays a crucial role in the melanin formation process, making it a key target in the formulation of skin-lightening agents. This study evaluated the potential of cream preparations containing ethanol extract of Kepel leaf (Stelechocarpus burahol) and pulasari bark (Alyxia reinwardii) as tyrosinase inhibitors. The extract is obtained through the maceration method using a 96% ethanol solvent and then formulated into a cream preparation with concentrations of 1.25% and 2.5%. Physical characteristics tests (viscosity, pH, dispersibility, adhesion, homogenity) and tyrosinase enzyme inhibition activity tests were performed in vitro using ELISA instruments or microplate readers. The results showed that increased concentration of the extract affected the physical properties of the preparation and increased inhibition ability against tyrosinase, but statistical tests showed insignificant differences in results. Formulations with a concentration of 2.5% showed the highest activity in inhibiting tyrosinase, with pulasari bark extract being more effective than kepel leaves. These findings strengthen the potential of both plants as active ingredients in natural-based skin lightening cosmetic products